Performance of existing prognostic factors for colorectal cancer prognosis - a critical view - Sarkar M., (Institutional Knowledge at Singapore Management University, 2001)
Physicians use several prognostic factors to determine the state of a patient who is in the follow-up program of colorectal cancer. Casting this prognosis problem as a pattern classification problem, we have attempted to find how efficient the prognostic factors are for the classification. We have specifically chosen sixteen most important prognostic factors for conducting experiments. The experimental results show with strong evidence that the chosen prognostic factors have limited discriminatory capability, and hence their use in prognosis may not improve the prognostic efficiency satisfactorily. We present the data analysis and experimental results based on the real data collected from Singapore General Hospital.